Partisipasi Petani dalam Pengelolaan Hutan Rakyat di Desa Benteng Kabupaten Bogor Provinsi Jawa Barat - Hudiyani, Indiyah (Jurnal Penyuluhan, 2015)
The existence of private forest today is an important role, especially to supply the demand of wood and to improve the environment quality.Participation of farmers is very important to developing the private forest. The farmers have been developing private forest since 2005, when The Ministry of Forestry had a program National Mobilitation of Rehabilitation in forest and land. The utilization of private forest is to be a saving for the farmers. The goals of this research was to analyzed the level participation of farmers in managing private forest and to identified the factors that correlated with the participation of farmers in managing private forest. The data were collected on Oktober-Nopember 2013 in Benteng Village, Ciampea Sub District Bogor District West Java Province using some methods: questioner list, observasion, depth interview, and documents. The data were analyzed using non parametric statistic, based on Rank-Spearman correlation test using SPSS 20 software programming. The results showed that participation of farmers in managing private forest were low and the factors that affected the participation of farmers were width of the private forest , income, motivation, forestry extension, dan the supporting from the group of farmers.Keywords: participation of farmers, private forest